Managing capital flows in an economic community: The case of ASEAN capital account liberalization - Yung Chul Park; Shinji Takagi (Asian Development Bank Institute (ADBI), 2012)
The paper uses the emerging Association of Southeast Asian Nations (ASEAN) Economic Community as a motivation to explore the issue of capital flow management in an economic community. Although there is an increasingly shared view that capital flow management measures should be part of the routine policy toolkit of emerging market economies, the logic of an economic community appears incompatible with extensive controls on capital flows. Substantial, if not complete, capital account liberalization must therefore take place across ASEAN. Few ASEAN countries are expected to have dismantled all capital account restrictions by 2015, thus requiring little need to introduce an entirely new set of capital flow management measures. Over the longer term, the ultimate requirements of an economic community seem to dictate that any remaining measures be market-based and not residency-based. Regional cooperation would be useful in enhancing individual country efforts, including collectively agreeing on the definition of a crisis and affirming the right of a member country to introduce an emergency measure in the event of a crisis. Our assessment is that most of the inflow restrictions could be removed quickly without creating additional risks; controls on private capital outflows could also be relaxed, albeit more judiciously, if for no other reason than to promote regional financial integration.
Keywords: F33; F36; O53; 330; managing capital flows; economic community: asean; capital account liberalization; emerging market economies; Kapitalmobilität; Kapitalverkehrskontrolle; Kapitalbilanz; ASEAN-Staaten